2016
DOI: 10.1111/ijd.13226
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide treatment of cutaneous lupus erythematosus: the Mayo Clinic experience

Abstract: Lenalidomide was effective for the treatment of CLE (particularly DLE) but not for the treatment of lupus panniculitis in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…For example, in addition to the in vitro inhibitory effect of these compounds on TLR-induced cytokine and type 1 IFN production (5, 7), clinical studies have shown IMiDs to be effective in the treatment of immunological disorders, including cutaneous lupus erythematous and multiple sclerosis (18,19). However, although the therapeutic potential of IMiDs is widely recognized, concerns over teratogenicity have restricted their wider use in the treatment of sublethal diseases, including inflammatory and autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in addition to the in vitro inhibitory effect of these compounds on TLR-induced cytokine and type 1 IFN production (5, 7), clinical studies have shown IMiDs to be effective in the treatment of immunological disorders, including cutaneous lupus erythematous and multiple sclerosis (18,19). However, although the therapeutic potential of IMiDs is widely recognized, concerns over teratogenicity have restricted their wider use in the treatment of sublethal diseases, including inflammatory and autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, analogues of thalidomide have been developed in order to avoid the undesired side effects. Of these, lenalidomide displayed similar efficacy and relapse rates as thalidomide [67][68][69][70][71][72], and iberdomide (CC-220) improved significantly moderate-to-severe lupus skin manifestations [73]. Lenalidomide has greater immunomodulatory properties than thalidomide, being more potent in the stimulation of T-cell proliferation and IFN-γ/IL-1 production [74].…”
Section: Limited Clinical Use Of Thalidomide In Dle: Need Of Novel Samentioning
confidence: 99%
“…with sunscreens, topical corticosteroids, and antimalarial agents is often effective. However, immunosuppressive and/or immunomodulatory agents may be required for recalcitrant disease (Kindle et al, 2016).…”
Section: Therapymentioning
confidence: 99%
“…Cutaneous Lupus Erythematosus (CLE) can be divided into three main subtypes: acute, subacute, and chronic, all of them demonstrate photosensitivity. Acute Cutaneous Lupus Erythematosus (ACLE) most commonly presents as symmetric erythema overlying the malar cheeks and nasal bridge with sparing of the nasolabial folds (butterfly rash) (Kindle et al, 2016).…”
mentioning
confidence: 99%